Портрет підприємця новітньої формації в сучасних соціокультурних умовах - Олексенко, Роман Іванович; Олексенко, Роман Иванович; Oleksenko, Roman (My University, 2015)
UK: У статті розкритий вплив соціокультурної детермінації як механізм адаптації до середовища. Суспільство виробляло подібні механізми протягом всієї культурної історії. Оскільки економічні відносини відомі впродовж тисячоліть, то в кожну історичну епоху вони супроводжувалися певними нормами і правилами, які регулюють увесь економічний процес: від виробництва до споживання. RU: В статье раскрыто влияние социокультурной детерминации как механизм адаптации к среде. Общество производило подобные механизмы в течение всей культурной истории. Поскольку экономические отношения известны на протяжении тысячелетий, то в каждую историческую эпоху они сопровождались определенными нормами и правилами, регулирующими весь экономический процесс: от производства до потребления. EN: The article deals with the problem of human existence in sociocultural space between globalization and the information revolution. As history shows, entrepreneurs – people who have the ability to signifi cantly affect the economic and social situation of the country and create her image in the international business world. In the socio-economic systems, there are certain «management tools»: hierarchy (organization), where the primary means of infl uence – pressure on a person with the help of coercion; culture; market. Along with «market management tools it» is important to develop management tools «cultural» management tools(instruments). The formation of market relations period of «primitive accumulation of capital» becomes more civilized direction. The more civilized a society is, the more it is culture of entrepreneurship. In modeen society? The sihiation produces an increased interest of the individual to his social position and desire to change by changing social positions. We can assume that the term «entrepreneur» in the everyday sense, get all members of society who committed the transition from one to the other social relations that changed their social status and place in the social division of labor. The modern entrepreneur is economicperson, formed under the previous – industrial – civilizational matrix was value oriented primarily to benefi t and profit extraction, production and multiplication of wealth, a status of consumption. With much focus and diversity of interests, needs and passions modern entrepreneur is characterized by such features as effi ciency, initiative, creativity. They allow people of new economic structure to stand out in the a general social structure as the most active subject of social and cultural development.
Портрет предпринимателя новой формации в социокультурных условиях
Portrait of a businessman in a formation of a new sociocultural conditions
Keywords: підприємець; суспільство; підприємство; культура; предприниматель; общество; предприятие; культура; businessman; community; businessandculture